Electrical Characterization of Metal–Semiconductor Au/Alpc-H/P-Si/Al Organic Diode - Missouma, I.; Benhaliliba, M. (Algerian Journal of Research and Technology (AJRT), 2017)
The Au/AlPc-H/p-Si/Al organic diodes based on Al-phthalocyanine diodes are fabricated by the spin coating process onto p-type silicon substrate. The Au/AlPc-H contact is thermally evaporated in vacuum at 10-6Torr. Here, we investigate the electronic parameters obtained from the current-voltage (I-V) characteristics achieved at room temperature under dark conditions within the -1V, +1V bias voltage range. The Cheung’s and Norde approximations are used for the calculation of the electronic magnitudes. The obtained values, such as ideality factor (n), barrier height (Φb) series resistance (RS), are approximately similar which approve the consistency of Cheung's and Norde methods. The I–V forward bias in log scale has been investigated to explore the dominated conduction mechanism. The AlPc Hydroxide/ p-Si contacts exhibit high rectification ratio (RR) in order of 2.73×104 and large ideality factor of 7.37.